Genomics of adverse drug reactions - Cardoso, Maria Luís (2021)
Adverse events related to COVID-19 vaccination have been hotly debated since the beginning of this year. However, despite the general interest on COVID-19 vaccines adverse events, they are much less frequent than adverse drug reactions (ADRs) occurring with other classes of drugs. ADRs are an important cause of morbidity and mortality with high economic, personal and societal consequences. The susceptibility of experiencing such events is dependent on environmental, clinical and genetic factors. There has been significant progress in the context of ADRs investigation. Most of the genes currently studied code for metabolizing enzymes or transporters that influence drugs pharmacokinetics. The identification of variants in these genes allows the categorization of patients as poor, intermediate, extensive, and ultra-fast metabolizers. To a lesser extent, the genes coding for drug targets, pharmacodynamics, are also examined. Recent studies have revealed associations between some human leukocyte antigens (HLA) and predisposition to immune-mediated ADRs too. Genomic testing can help to predict and prevent ADRs, improving the benefit /risk ratio of drug therapy. We expect that our research will contribute with important evidence and tools to promote pharmacogenomics use in healthcare system for ADRs prevention.